Glucose-dependent effect of insulin receptor isoforms on tamoxifen antitumor activity in estrogen receptor-positive breast cancer cells - Stella, Stefania; Massimino, Michele; Manzella, Livia; Parrinello, Nunziatina Laura; Vitale, Silvia Rita; Martorana, Federica; Vigneri, Paolo (Frontiers in Endocrinology, 2023)
Introduction Breast cancer is the most common malignancy in women, and it is linked to several risk factors including genetic alterations, obesity, estrogen signaling, insulin levels, and glucose metabolism deregulation. Insulin and Insulin-like growth factor signaling exert a mitogenic and pro-survival effect. Indeed, epidemiological and pre-clinical studies have shown its involvement in the development, progression, and therapy resistance of several cancer types including breast cancer. Insulin/Insulin-like growth factor signaling is triggered by two insulin receptor isoforms identified as IRA and IRB and by Insulin-like growth factor receptor I. Both classes of receptors show high homology and can initiate the intracellular signaling cascade alone or by hybrids formation. While the role of Insulin-like growth factor receptor I in breast cancer progression and therapy resistance is well established, the effects of insulin receptors in this context are complex and not completely elucidated. Methods We used estrogen-dependent insulin-like growth factor receptor I deleted gene (MCF7IGFIRKO) breast cancer cell models, lentivirally transduced to over-express empty-vector (MCF7IGFIRKO/EV), IRA (MCF7IGFIRKO/IRA) or IRB (MCF7IGFIRKO/IRB), to investigate the role of insulin receptors on the antiproliferative activity of tamoxifen in presence of low and high glucose concentrations. The tamoxifen-dependent cytotoxic effects on cell proliferation were determined by MTT assay and clonogenic potential measurement. Cell cycle and apoptosis were assessed by FACS, while immunoblot was used for protein analysis. Gene expression profiling was investigated by a PCR array concerning genes involved in apoptotic process by RT-qPCR. Results We found that glucose levels played a crucial role in tamoxifen response mediated by IRA and IRB. High glucose increased the IC50 value of tamoxifen for both insulin receptors and IRA-promoted cell cycle progression more than IRB, independently of glucose levels and insulin stimulation. IRB, in turn, showed anti-apoptotic properties, preserving cells’ survival after prolonged tamoxifen exposure, and negatively modulated pro-apoptotic genes when compared to IRA. Discussion Our findings suggest that glucose levels modify insulin receptors signaling and that this event can interfere with the tamoxifen therapeutic activity. The investigation of glucose metabolism and insulin receptor expression could have clinical implications in Estrogen Receptor positive breast cancer patients receiving endocrine treatments.